Are We There Yet? : The Myths and Realities of Autonomous Vehicles. - Pagano, Michael A. (The Urban Agenda Ser., 2020)
"Autonomous vehicle (AV) technology represents a possible paradigm shift in our way of life. But complex challenges and obstacles impose a reality at odds with the utopian visions propounded by AV enthusiasts in the private and public sectors. This book examines the technological questions still surrounding autonomous vehicles and the uncertain societal and legislative impact of widespread AV adoption. Assessing both short- and long-term concerns, the authors probe how autonomous vehicles might change transportation but also land use, energy consumption, mass transit, commuter habits, traffic safety, job markets, the freight industry, and supply chains. At the same time, the essays discuss opportunities for industry, researchers, and policymakers to make the autonomous future safer, more efficient, and more mobile"--